HUBUNGAN PENGETAHUAN AWAL MATEMATIKA DENGAN KEMAMPUAN LITERASI MATEMATIS PESERTA DIDIK DI SEKOLAH DASAR (SD) - Mustari, Facharuddin; La Tike; Hamdiansah; Iman Ashari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the relationship between initial knowledge of mathematics and the mathematical literacy abilities of students in elementary school. The problem formulation for this research is whether there is a relationship between initial knowledge of mathematics and mathematical literacy abilities. This research uses a quantitative method which is associative correlation. The population of this study was all students at SD Negeri 100 Kendari. The research sample was class V.A which was determined using a purposive sampling technique. The research instruments used were initial mathematics knowledge test questions and mathematical literacy ability test questions. The data collection technique was carried out using the test method. Data were analyzed using correlation analysis. Based on the results of the analysis, a positive, strong and significant relationship was obtained between initial knowledge of mathematics and the mathematical literacy abilities of class V.A students at SD Negeri 100 Kendari with a correlation of rxy = 0.733. This value is in the coefficient interval 0.600 – 0.799 with positive strong relationship in a positive direction. The results of the significance test analysis on this research data obtained a tcount value of 4.168 while the ttable value was obtained at 1.75. So the value of tcount > ttable which means that there is a significant relationship between initial knowledge of mathematics and initial mathematical abilities of class V.A students at SD Negeri 100 Kendari. The results of data analysis in this study obtained a determination coefficient of 53.7%. This means that the contribution of initial mathematics knowledge to the mathematical literacy skills of students in class V.A of SD Negeri 100 is 53.7%. The remaining 46.3% is influenced by other factors.